Generational differences, work-life balance and wellbeing in European countries - Sousa, Cristina; Ferreira, Pedro (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Generational issues have been one of the most prevalent topics in the last decade about the mutations affecting workforce. The importance of this topic is anchored on the entry into the labour market of the latest generation, known as generation Y or millennials. This is an important and unprecedented change, since it means that three different generations are simultaneously present and interacting in the labour market and in the workforce, raising several questions and challenges for organizations, specifically for Human Resource Management (HRM) professionals. The awareness of this challenge has led many researchers and practitioners to look at the characteristics that define the new generation, their work values, expectations and drives. Generational approaches to work and HR related subjects tend to be either strictly focused on generation Y (Ertas, 2015; (Broadbridge, Maxwell, & Ogden, 2007; Kultalahti & Liisa Viitala, 2014; Ng, Schweitzer, & Lyons, 2010; Weber, 2015), or use cross-generational comparisons to better understand Yers’ motivations, work values and attitudes (Cennamo & Gardner, 2008; Chen & Choi, 2011; Twenge, Campbell, Hoffman, & Lance, 2010). While this focus offers a better understanding of the new generation – entering the labour market since the beginning of 2000 and will continue to enter until 2022 – it simultaneously overshadows research on previous generations. Moreover, the general approach has been too narrow and most studies focus on investigating generation Y and generational differences within a confined single cultural context. Although this approach is insightful in terms of a specific socio-cultural context, offering a localized perspective on generational changes, it does miss the cross-cultural richness of comparing the underlying dynamics of different cultural background in building generational differences and characteristics. As Hofstede (2001) emphasized cultures and all their subsequent phenomena only exist in comparison to other cultures. This is also valid for the world of work. Work-life balance (WLB) is widely studied topic in human resources management (HRM). As a part of wellbeing, many worldwide organisations, such as the OECD, have been calling to the fore the importance of fostering people’s wellbeing and work-life balance. Within organizational studies, the preferred approaches have examined how organizational factors impact on WLB, namely HRM practices (Guest, 2002). Despite the extensive research on the topic, there is still a lack of understanding about the extent to which external factors affect WLB. Although work-life balance is made of “work” and “life” (meaning all other personal dimensions of a worker’s life), research tends to focus more on the “work” and less on the “life” dimension. This provides the scenario for the present study, which aims to examine how different generations perceive wellbeing and work-life balance, using a cross-cultural approach. Specifically, besides the general differences between generations and how this affects wellbeing perception, this study seeks to quantitatively map and assess potential differences across Europe, concluding with a portrait of different generational profiles within the continent. For that purpose the paper uses data from the 2010 European Social Survey (ESS5). The data, covering 28 countries, is based on long face-to-face interviews with 52458 persons aged 15 or more years, which include a module on Work, Family and Wellbeing.